2020
DOI: 10.1177/0391398820962112
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of age, diabetes, gender, and access type on costs associated with vascular access among Chinese patients on hemodialysis

Abstract: Objectives: Examine the impacts of age, diabetes, gender, and access type on vascular access (VA) associated costs among Chinese hemodialysis (HD) patients. Methods: We retrospectively included patients whose first permanent VA was created at the West China Hospital. Clinical characteristics, maturation, intervention, utilization, and exchange of every VA, as well as VA-related infection were collected. The study period for each patient was from HD initiation to the last follow-up. VA-related costs, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Numerous studies have confirmed that DM is an important risk factor for the poor prognosis of patients on MHD [ 7 ]. Similar results have also been obtained in the Chinese MHD population [ 8 ]. Therefore, considering the prognosis of such patients is important; however, current treatment options are limited to dietary and risk factor interventions and the control of complications.…”
Section: Introductionsupporting
confidence: 88%
“…Numerous studies have confirmed that DM is an important risk factor for the poor prognosis of patients on MHD [ 7 ]. Similar results have also been obtained in the Chinese MHD population [ 8 ]. Therefore, considering the prognosis of such patients is important; however, current treatment options are limited to dietary and risk factor interventions and the control of complications.…”
Section: Introductionsupporting
confidence: 88%
“…Based on research, patients with dM who use temporary vascular access are considered more susceptible to infection and sepsis. 6 Installation of NtHc is an action that is often done in rsud dr. soetomo surabaya and there has been no study on the duration of the hemodialysis catheter patency installed in rsud dr. soetomo, surabaya. data collection and publications related to the condition of existing patients are limited in rsud dr. soetomo, surabaya.…”
Section: Documents Year Valuementioning
confidence: 99%